2021
DOI: 10.3390/en14164873
|View full text |Cite
|
Sign up to set email alerts
|

PV Energy Communities—Challenges and Barriers from a Consumer Perspective: A Literature Review

Abstract: Renewable energy sources, in particular those based on solar radiation, are growing rapidly and are planned to play an instrumental role in building power systems to reach the 2030 and 2050 energy and climate mitigation objectives. However, new actors have been introduced into the energy field, highlighting the importance of the role of citizens and communities in building such energy systems. To outline the significance of citizens in the development of solar energy communities and to describe the benefits of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…Research shows that one of the key solutions to prevent high energy poverty levels would be to promote local generation [50], offering consumers the possibility to become energy producers (prosumers) or to provide non-discriminatory participation opportunities to participate in the energy community. In addition, consumer participation in local energy production would motivate them to significantly change their usual electricity consumption, thus, promoting energy efficiency and development of new services, such as demand response activities [51].…”
Section: Latviamentioning
confidence: 99%
“…Research shows that one of the key solutions to prevent high energy poverty levels would be to promote local generation [50], offering consumers the possibility to become energy producers (prosumers) or to provide non-discriminatory participation opportunities to participate in the energy community. In addition, consumer participation in local energy production would motivate them to significantly change their usual electricity consumption, thus, promoting energy efficiency and development of new services, such as demand response activities [51].…”
Section: Latviamentioning
confidence: 99%
“…Despite the holistic view proposed in this article, most of the published systematic literature reviews linked to solar PV have showed a technical focus, covering topics such as: advances in solar cell research and testing [18][19][20][21], energy losses and degradation of PV modules [22][23][24], forecasting of solar photovoltaic radiation and electricity generation [25,26], digital technologies for PV monitoring [27], and leaching of metals from EOL PV waste [28,29]. Other review articles have been more market-oriented, highlighting the need for government interventions in supporting PV diffusion [30]; the factors influencing residential households' adoption of PV systems [31,32]; and descriptions of the current PV market, its associated costs, and available technologies [33]. Finally, a growing stream of literature focusing on the management of EOL PV modules has also emerged.…”
Section: Analytical Framework and Related Literaturementioning
confidence: 99%
“…This distinct quantity of PV generation, electricity tariffs, and support policies generate different self-consumption benefits. However, the high investment cost of the necessary equipment and installation is still a big challenge in facilitating the integration, at a big scale, of this kind of energy generation solution [35]. Thus, it can be said that ECs are still in their infancy, as some EU and non-EU member states did not transpose the definition to their law yet or implemented clear aids to facilitate a wide implementation of self-consumption systems at the end-user level.…”
Section: Introductionmentioning
confidence: 99%